Effect of Growth Mode on Eu-Incorporation and Luminescence of Eu-Doped GaN Epitaxial Film Grown by Plasma-Assisted Molecular Beam Epitaxy - Park, Ji-Ho; Wakahara, Akihiro; Okada, Hiroshi; Sekiguchi, Hiroto; Tiwari, Ajay; Kim, Yong-Tae; Song, Jonghan; Lee, Jong-Han; Jhin, Junggeun (IOP PUBLISHING LTD, 2011)
The growth mode of europium (Eu)-doped GaN epitaxial films grown on a GaN template by rf plasma- assisted molecular beam epitaxy (PAMBE) was investigated with different III/ V ratios under a constant Eu beam equivalent pressure ratio [P-Eu/P-Eu + P-Ga)]. The reflection high-energy electron diffraction (RHEED) patterns and atomic force microscopy (AFM) images revealed the transition of the growth mode from threedimensional (3D) to step-flow/two-dimensional (2D) by increasing the III/V ratio. When the films were grown in the 3D growth mode, Eu concentrations estimated by Rutherford backscattering spectrometry/channeling (RBS/channeling) were almost constant, although the III/V ratios varied. However, when the growth mode was transferred from 3D to step-flow/2D, precipitates on the surface abruptly increased while the Eu concentration abruptly decreased, indicating the abrupt degradation of Eu-incorporation in the film. Luminescence sites of Eu3_ were sensitive to the III/V ratio, and Eu atoms have different luminescence sites in both growth modes. Furthermore, luminescence efficiency abruptly increased when the growth mode was transferred from 3D to step-flow/2D. (C) 2011 The Japan Society of Applied Physics
Keywords: LIGHT-EMITTING-DIODES; IMPLANTED GAN; III-NITRIDES; PHOTOLUMINESCENCE; ALXGA1-XN; ER; EMISSION; SURFACE; GREEN